Role of Mutation of NOTCH1 gene in development of oral squamous cell carcinoma: a narrative review - Quratulain Javaid; Usmani, Ambreen (Journal of the Pakistan Medical Association, 2024)
Cancer of the oral cavity has numerous types and, among all, oral squamous cell carcinoma represents >90% of all cancers of the oral area. Oral squamous cell carcinoma arises from the squamous lining of the oral cavity. Across the globe, most commonly it develops in the regions of tongue followed by floor of the mouth, and lower lip. Neurogenic locus notch homolog protein 1 gene has its association with oral squamous cell carcinoma and is known to be associated with both oncogenic and tumour suppressor roles. The current narrative review comprised literature published from 2013 to 2023. It was searched on Google Scholar, PubMed and Google databases. Globally, neurogenic locus notch homolog protein 1 mutations are associated with the development of oral squamous cell carcinoma. Most of the mutations are linked to ligand bind epidermal growth factor-like repeat region of extracellular domain of neurogenic locus notch homolog protein 1. —Continue